2022
DOI: 10.3390/foods11091368
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Effects from Ultrasound Thawing, Vacuum Thawing and Microwave Thawing on the Quality Properties and Oxidation of Porcine Longissimus Lumborum

Abstract: The effects of vacuum thawing (VT), ultrasound thawing (UT) and microwave thawing (MT) on the quality, protein and lipid oxidation, internal temperature distribution and microstructure of porcine longissimus lumborum were compared. The results showed that a significant decrease (p < 0.05) in quality compared with those of fresh meat (FM) occurred for all of the thawing samples, especially for the MT samples. Changes in quality of the VT and UT samples were less significant than those of the MT samples. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…For ultrasound combined with plasma-activated water treatment accelerated the lipid oxidation of chicken, suggesting that the antioxidant enzymes remaining in chicken cannot defend against the action of reactive species in PAW when the integrity of chicken tissue was destroyed by ultrasound ( Qian et al, 2022 ). Wang et al (2022) and Li et al (2023) similarly found that ultrasound thawing promotes lipid oxidation. But there are also some studies that ultrasound can inhibit lipid oxidation ( Cai et al, 2020 , Gan et al, 2022 ), for which more in-depth research may be needed.…”
Section: Resultsmentioning
confidence: 93%
“…For ultrasound combined with plasma-activated water treatment accelerated the lipid oxidation of chicken, suggesting that the antioxidant enzymes remaining in chicken cannot defend against the action of reactive species in PAW when the integrity of chicken tissue was destroyed by ultrasound ( Qian et al, 2022 ). Wang et al (2022) and Li et al (2023) similarly found that ultrasound thawing promotes lipid oxidation. But there are also some studies that ultrasound can inhibit lipid oxidation ( Cai et al, 2020 , Gan et al, 2022 ), for which more in-depth research may be needed.…”
Section: Resultsmentioning
confidence: 93%
“…As the ice crystals are formed from the extracellular to the intercellular, a large amount of electrolyte is concentrated in the extracellular part. Consequently, intracellular water is released into the extracellular part through osmotic pressure [ 25 ]. Additionally, the differences in the color and visible appearance of meat analogs were not affected by the freezing temperature difference (−18 °C and −60 °C).…”
Section: Resultsmentioning
confidence: 99%
“…Finding that the ultrasound thawing preserves the quality. [98] The USI thawing process offers advantages regarding no food damage, minimal water loss, no microbial contamination, and lower protein denaturation. Furthermore, it enhances the thawing rate of a range of frozen products, reducing the thawing time and preserving the color, pH, and lipid oxidation.…”
Section: Ultrasonic Freezing-thawingmentioning
confidence: 99%